Prediction and modeling of underwater noise in Australian shallow water environments - Koessler, M.; Duncan, Alec; Gavrilov, Alexander (2015)
Predictive underwater noise modeling is often required as part of the regulatory approval process for marine industrial operations. In Australia modeling is used to assess the potential environmental impacts of operations that take place within the country's exclusive economic zone. A physics based modeling approach is used to predict the sound energy levels produced by a source in the ocean interior. Our aim is to best predict sound exposure levels (SELs) from impulsive sources such as seismic survey airgun arrays and pile drivers. Large portions of the continental shelf and upper slope around Australia are characterized by small amounts of unconsolidated sediments over cemented sediments. The extent of this environment makes it unusual on a global scale. Sound propagation modeling considering these types of sea bottoms is non-trivial and is an active area of research. In this article, an overview of the modeling procedure used to produce SEL predictions is presented and discussed. This discussion includes the influence of environmental factors such as range dependence, the geoacoustic properties of seafloor sediment, along with the computational methods that we have found to be appropriate for this type of environment. A case study involving the prediction of underwater noise from an offshore seismic survey is presented as an example of the application of this produce.